2020
DOI: 10.1038/s41467-020-18982-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and systematic review of reported neonatal SARS-CoV-2 infections

Abstract: A number of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections have been reported in neonates. Here, we aim to clarify the transmission route, clinical features and outcomes of these infections. We present a meta-analysis of 176 published cases of neonatal SARS-CoV-2 infections that were defined by at least one positive nasopharyngeal swab and/or the presence of specific IgM. We report that 70% and 30% of infections are due to environmental and vertical transmission, respectively. Our anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
297
4
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(367 citation statements)
references
References 106 publications
(251 reference statements)
24
297
4
23
Order By: Relevance
“…In addition, increasing numbers of global cohort studies of pregnant women with COVID-19 that examine neonatal outcomes have demonstrated that a small percentage of newborn infants will test positive for SARS-CoV-2 following birth. In a recent meta-analysis of 74 publications, there were a total of 176 neonates from around the world who tested positive for SARS-Cov-2 [51]. Of these, 174 were diagnosed using RT-PCR methods, and 2 diagnosed by the presence of IgM in newborn blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increasing numbers of global cohort studies of pregnant women with COVID-19 that examine neonatal outcomes have demonstrated that a small percentage of newborn infants will test positive for SARS-CoV-2 following birth. In a recent meta-analysis of 74 publications, there were a total of 176 neonates from around the world who tested positive for SARS-Cov-2 [51]. Of these, 174 were diagnosed using RT-PCR methods, and 2 diagnosed by the presence of IgM in newborn blood.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, transplacental vertical infection appears to be uncommon. In a recent analysis, Raschetti and colleagues have estimated that among neonates testing positive for COVID-19, 70% are due to postpartum environmental exposure, and 30% result from prenatal vertical infection [51]. The authors expounded on these metrics by estimating that among all neonates testing positive for COVID-19, approximately 9% represented confirmed prenatal vertical infections −3.3% for intrapartum acquisition and 5.7% for congenitally (intrauterine) transmitted infections.…”
Section: Discussionmentioning
confidence: 99%
“…Since, several articles have reported that the possibilities of vertical transmission (37,38), highlighting the importance of long-follow up of newborns (39). To clarify the vertical transmission and neonatal outcomes due to SARS-CoV-2 infection; we further compared our findings with other recently published systematic review and meta-analyses (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Raschetti et al (38) evaluated neonatal outcomes from 74 published articles in where 30% of neonates were reported in the possible vertical transmission and 70% were from environmental sources ( Table 4).…”
Section: Comparison With Recent Findingsmentioning
confidence: 99%
“…According to the initial available literature, the risk of vertical transmission is 5-30% but may be underreported due to lack of early diagnosis. ACE2 receptors and TMPRSS2 molecules are highly expressed in placenta and the expression peaks at term and the virus often invade the placenta and rarely cause miscarriage [16][17][18][19]. From two different case series, 4 infants had positive nasopharyngeal SARS-CoV-19 RT-PCR within 2 days of life, but cord blood, amniotic fluid and cord blood samples were negative in these infants [20,21].…”
Section: Transmission Of Covid-19mentioning
confidence: 99%